2018
DOI: 10.1038/s41598-018-20114-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of cardiomyopathy and the genotypes involved in prognosis and left ventricular reverse remodeling

Abstract: Dilated cardiomyopathy (DCM) and hypertrophic cardiomyopathy (HCM) are genetically and phenotypically heterogeneous. Cardiac function is improved after treatment in some cardiomyopathy patients, but little is known about genetic predictors of long-term outcomes and myocardial recovery following medical treatment. To elucidate the genetic basis of cardiomyopathy in Japan and the genotypes involved in prognosis and left ventricular reverse remodeling (LVRR), we performed targeted sequencing on 120 DCM (70 sporad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
103
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 36 publications
8
103
1
Order By: Relevance
“…LMNA genotype-positive subjects seem to have a younger age of diagnosis of DCM and larger left atrial than those negative patients, but the outcome difference was not significant. www.nature.com/scientificreports www.nature.com/scientificreports/ Our study showed that about one third DCM patients carried pathogenic or likely pathogenic variants, a frequency similar to those reported in in Japanese and Finish populations 8,13 . TTN truncating variants remain the most common variants in our Chinese cohort.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…LMNA genotype-positive subjects seem to have a younger age of diagnosis of DCM and larger left atrial than those negative patients, but the outcome difference was not significant. www.nature.com/scientificreports www.nature.com/scientificreports/ Our study showed that about one third DCM patients carried pathogenic or likely pathogenic variants, a frequency similar to those reported in in Japanese and Finish populations 8,13 . TTN truncating variants remain the most common variants in our Chinese cohort.…”
Section: Discussionsupporting
confidence: 86%
“…Akinrinade and colleagues concluded in the Finnish population that adverse outcomes in patients with TTN truncating variants were indistinct from those other gene variant groups except LMNA variants 8 . In several other studies, however, patients with TTN truncating variants were reported to be less severe at presentation and to be associated with a favorable response to treatment than patients with LMNA variants or patients negative for TTN and LMNA genes 13,19 . Altogether, the published data on genotype-phenotype associations in DCM cannot provide a clear correlation between TTN truncating variants and clinical phenotype.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…[55] have found that deletion of pyruvate dehydrogenase kinase 4 (PDK4) prevented angiotensin II-induced cardiac hypertrophy and improved cardiac glucose oxidation and energy usage. MeSH-based disease analysis demonstrated that significant changes in cardiomyocyte genes (decreased MYL2 and MYH6 and increased RYR2, HCN4, CORIN, NPPA, ERBB2, and MYH7) in LV of obese ZSF1 rats were strongly associated with dilated cardiomyopathy, LV hypertrophy, and HF (Fig 5F), and were similar to those observed in human genetic studies [56]. The array of expression changes in LV heart abundant genes in obese ZSF1 rats would help us to better understand the cardiac metabolic shift and cardiomyopathy in CMS; to allocate the major players mediating the crosstalk between glucose, lipid metabolism, and development of CVD; and to potentially identify key markers of cardiac energy status and heart injury grade.…”
Section: Discussionsupporting
confidence: 82%
“…Target enrichment system and next-generation sequencing technologies have enabled simple and efficient comprehensive gene screening for cardiomyopathy. Recent comprehensive targeted sequencing studies showed that approximately 40% of patients with DCM have pathogenic mutations in genes reported to be causal for cardiomyopathy [4,5]. Although there are some ethnic differences in the proportion of mutated genes, titin (TTN) truncating mutations and lamin A/C (LMNA) mutations are considered to be major factors for the development of DCM.…”
Section: Genomic Architecture Of Cardiomyopathymentioning
confidence: 99%